Total phenolic and flavonoid contents and antioxidant activities of extracts from Teucrium polium growing wild in Morocco. (2019) - El Atki, Y.; Aouam, I.; El kamari, F.; Taroq, A.; Lyoussi, B.; Taleb, M.; Abdellaoui, A.
Abstract: The objective of the present study was to determine antioxidant activities, total phenolic and total flavonoid contents of methanol, ethanol, water and ethyl acetate extracts of Moroccan Germander ( Teucrium polium ). Total phenolic and flavonoid contents were determined spectrophotometrically using gallic acid and rutin as standards. Antioxidant activities was evaluated in vitro by three assays namely free radical scavenging activity against 1, 1-diphenyl-2-picrylhydrzyl (DPPH), ferric reducing antioxidant power (FRAP) and total antioxidant capacity. The total phenolic and flavonoid contents were significantly higher in the methanolic extract (P<0.05) than all other extracts. The methanolic extract showed the highest antioxidant activity as measured by DPPH and FRAP assays with IC50 values of 0.41 ± 0.03 mg/ml and 0.21 ± 0.002 mg/ml respectively. The total antioxidant capacity test showed that the water extract had a significant activity with value of 129.5 ± 3.19 mg equivalent to ascorbic acid/g dry weight. However, the ethyl acetate extract had a weak antioxidant effect in the three tests. A significant correlation between antioxidant activities and contents of polyphenols and flavonoids was found. These results showed that Moroccan Germander have a great relevance in the prevention and treatment of diseases in which free radicals are implicated.